The effect of flow experience on reuse intention of mobile navigation apps: The mediating role of location-based mobile service quality - Erdem Ozkan; Bahar Yasin; Aylin Ecem Gursen; Habib Mehmet Akpinar (Tourism & Management Studies)
This study aims to determine the effect of consumers' flow experience on their intention to reuse mobile navigation apps and reveal the mediating role of location-based mobile service quality in this effect. Data were collected through an online survey of 513 respondents who were actively using mobile navigation apps and analyzed using structural equation modeling and mediation analysis. The results reveal that flow experience affects the intention to reuse mobile navigation apps and that location-based mobile service quality mediates this effect. When the mediating role of location-based service quality was tested, the direct effect of flow experience on reuse intention became insignificant. Information, reliability, and design quality are the most significant dimensions of location-based service quality. Considering the limited number of studies on mobile navigation services, particularly user behavior, this study contributes substantially to services marketing literature. In addition, this study provides insights for practitioners on how to design service proposals and the realization processes of mobile navigation apps.